(3CjGJ GdeJhSejfs - (3GdMSjfj, GdMdj, GdfLaj, GdbRhjfj, eMeO egOj Hf GdMSf, J (B1300(3g`s ((3YHO GdgGOj Hf YHO Ydj Bd GdTjN NVQs)
(3ChdgG (B:s
(3NGJeI ajeG jJQJH Ydi GdeHOC hGdeYGO, hajg JhSeGJ GdJhSe GdChd aj GdYOds
(3BNQgG (B:s
(3hEfeG jehJhf OaYI hGMOI hgh YHGQI Yf QaYge Edi GdSeGA YfO bjGe GdSGYI aJCed(B. (3gPG eG CQOfG EjQGOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B114s
(3GdCYdGe(B: (3L(B7(3, U(B114s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds